2002
DOI: 10.1007/s00264-002-0381-1
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular roof reconstruction with pedicled iliac graft

Abstract: Reconstruction of the acetabular roof in patients with hip dysplasia shows disappointing mid-term results due to insufficient incorporation and collapse of the bone graft. We have developed a new reconstructive method using a pedicled iliac graft. We simulated surgical reconstruction of the acetabular roof in ten cadaver specimens. The purpose was to evaluate whether the deep circumflex artery was long enough to allow transfer of the graft without requiring micro-vascular anastomosis. In all cadavers, the leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…It allows superior acetabular exposure and proper cup placement. Several additional techniques can be used for cup placement in the true acetabulum such as cotyloplasty or acetabular roof reconstruction [7,8,11]. This approach also enables substantial lower extremity elongation [11] while preserving muscle continuity.…”
Section: Discussionmentioning
confidence: 99%
“…It allows superior acetabular exposure and proper cup placement. Several additional techniques can be used for cup placement in the true acetabulum such as cotyloplasty or acetabular roof reconstruction [7,8,11]. This approach also enables substantial lower extremity elongation [11] while preserving muscle continuity.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been few reports in the literature on the accuracy and reliability of digital templating in THA patients with dysplastic hips. THA is technically demanding in patients with dysplastic hips, especially the acetabular reconstruction; however, combining medialisation or proximalisation of the acetabular cup with various techniques for superolateral bone grafting can be helpful during total hip replacement for patients with dysplastic hips [6,7,17]. Bicanic et al reported that hip load decreased when the cup was placed more medially or distally in THA in patients with dysplastic hips [2].…”
Section: Discussionmentioning
confidence: 99%
“…For higher types of dysplastic hips, he recommend a structural bone autograft and use of an uncemented socket. Delimar et al [22] developed a new reconstruction method using a pedicle iliac graft after verifying that the deep circumflex artery was long enough to transfer this graft without resorting to micro-vascular anastomosis. Rozkydal et al [23] reported 43 cases of dysplastic hips treated with a CLS Expansion shell and a structural femoral head autograft.…”
Section: Discussionmentioning
confidence: 99%